Correlating thyroid cytology and histopathology: Implications for molecular testing. Issue 7 (21st February 2016) - Reed, Michael J.; Sperry, Steven M.; Gailey, Michael P.; Jensen, Chris S.; Robinson, Robert A.; Funk, Gerry F.; Pagedar, Nitin A.
ABSTRACT: Background: A gene expression classifier (GEC) has been advocated in management of some indeterminate nodules without surgery. We assessed the potential negative predictive value (NPV) of the GEC at our academic center. Methods: Retrospectively, all cytologically indeterminate fine‐needle aspirates (FNAs) diagnosed by University of Iowa cytopathologists over a 3‐year period were identified. Histopathologic findings were recorded. Using published sensitivity and specificity, NPVs were calculated. Results: Of 178 nodules (17, 135, and 26 in classes III, IV, and V, respectively), 71 (40%) were malignant. Prevalence of malignancy was 41%, 29%, and 96% for classes III, IV, and V, respectively. Using sensitivities and specificities for the GEC, NPVs were 91% for the cohort: 88%, 92%, and 26% for classes III, IV, and V, respectively. Conclusion: Molecular testing should be associated with an NPV no lower than that from clinical criteria alone. With the prevalences reported, GEC use may result in more missed cancer diagnoses. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1104–1106, 2016